Competitive adsorption between phosphate and dissolved organic carbon in iron-rich soils - Amenkhienan, Bright E.; Dijkstra, Feike A.; Singh, Balwant (Frontiers in Soil Science, 2025)
The competitive adsorption between phosphate and dissolved organic carbon (DOC) has been reported in Andosols and Podzols. However, the published results on the competitive adsorption between P and DOC are unclear and sometimes contradictory. The competitive behaviour between phosphate and DOC may be quite different in the surface and subsurface soils. In this study, we used surface and subsurface soils with substantial Fe oxide contents from Wagga Wagga (Chromosol) and Tumbarumba (Ferrosol) in New South Wales (Australia) to evaluate the adsorption behaviour of phosphate and DOC. Adsorption data were fitted into linear initial mass (IM) isotherm. The results showed that both surface and subsurface soils from Tumbarumba had a greater phosphate adsorption capacity than the soils from Wagga Wagga. Phosphate adsorption was greater for the subsurface soil (m = 0.72) than the surface soil (m = 0.82) from Tumbarumba, while this trend for was opposite for Wagga Wagga soils, where phosphate adsorption capacity was greater for the surface (m = 0.55) soil than the subsurface (m = 0.37) soil. The DOC adsorption was greater in the subsurface soils than the surface soils from both sites. In the mixed solution of P and DOC, phosphate adsorption promoted DOC desorption in the surface and subsurface soils from Wagga Wagga and Tumbarumba. The results of this study have crucial implications on the sustainability of Fe-rich soils. The adsorption of phosphate promoted DOC desorption in these soils, which may lead to the destabilisation of OC and impair OC sequestration and therefore enhance the microbial decomposition of OC in these soils.